PROVISION OF SOCIAL SERVICES TO THE POPULATION IN THE DEVELOPMENT OF SERVICE INFRASTRUCTURE OF UNITED TERRITORIAL COMMUNITIES - NYZHNYK, Viktor (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Modern policy in Ukraine is aimed at creating decent living conditions for the population and ensuring a high level of social benefits and services. One of the main tasks faced by specialists is solving the problem of providing the population with social benefits and services. A strategic direction of development is to improve the quality and efficiency of providing citizens with services such as healthcare, education, culture, housing and utilities, transportation, household services, and others. These components of the social sphere ensure a normal standard of living in united territorial communities (UTC). However, there are many obstacles to achieving these goals, such as insufficient infrastructure, weak financial base of local authorities, and the lack of a comprehensive system for reforming the social sphere. Despite numerous attempts, no Ukrainian government has successfully implemented a systemic policy to adequately reform the social sphere in UTCs. In the service sector, which satisfies citizens’ needs, it is important to ensure the effective development of economic and social relations in UTCs. The aim of this article is to analyze and justify the current state of social services provision in UTCs, identify the main problems in this area, and determine ways to address them. Specifically, the research is focused on improving mechanisms for regulating and financing social services, adapting the legal framework to European standards, and expanding the range of social services provided in line with the needs of the population and the socio-economic conditions of community development. To achieve this goal, it is necessary to address current issues and propose specific solutions to improve the quality of life in UTCs.